Building sustainable communities : environmental justice & global citizenship - Wulfhorst, J. D.; Haugestad, Anne K. (At the interface/probing the boundaries, 2006)
In this inter-disciplinary follow-up to Future as Fairness: Ecological Justice and Global Citizenship (edited by Haugestad and Wulfhorst, Rodopi 2004) 14 chapters explore a variety of conceptual and practical pathways to the building of sustainable communities. Five chapters provide different perspectives on sustainable and unsustainable agriculture. Other cases explored are wildlife valuations, distributional effects of environmental policy, the emerging American nuclear power renaissance, regulation of care use, job losses with a raising GDP, cooperation between labour and environmentalists.